Reduction of DC-Link Voltage Fluctuation for Hydraulic Turbine Generation Systems Using Back-to-Back Converters - Jeon, Sung Soo; Bak, Yeongsu; Lee, Kyo Beum (CENCON 2019 - 2019 IEEE Conference on Energy Conversion, 2019)
This paper proposes a reduction of DC-link voltage fluctuation for hydraulic turbine generation (HTG) systems using back-to-back (BTB) converters. In HTG systems, a BTB converters with two-level topology have been mainly used. Because of its strong points of being intuitive in circuit diagram and easy to maintain. A switch-open-fault in the grid-stage converter of the BTB converter causes the fluctuation of DC-link voltage in the BTB converters. It reduces the reliability of the HTG systems. To improve the performance of the HTG systems generally, supplementary circuits or components and tolerant control methods are required. Therefore, this paper proposed method to reduce the fluctuation of DC-link voltage when switch-open-fault is happened in the grid-stage converter. The validity of the proposed method to reduce the fluctuation of DC-link voltage is substantiated by simulation results.
Keywords: Back-to-back converter; BTB converters; Circuit diagrams; Control methods; DC-link voltages; Generation systems; Open faults; Back-to-Back (BTB) converter; Fluctuation of DC-link voltage; Hydrualic turbine generation (HTG) system; Switch-open-fault; Zero current of range